2018
DOI: 10.1149/2.0011807jes
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Synthesis of Biocompatible Pectin Stabilized Graphene Nanosheets Hydrogel and Their Application for the Simultaneous Electrochemical Determination of Dopamine and Paracetamol in Real Samples

Abstract: The development of novel and simple active sensing materials is still interested to fabricate a new and improved sensing devices for many industrial, medical and environmental applications. In this work, we have synthesized a new type of pectin (PT) and reduced graphene oxide (RGO) hydrogels (PT/RGO) by using simple sonochemical methods and further used as an active sensing material for simultaneous electrochemical detection of dopamine (DA) and paracetamol (AC). In general, PT and RGO have substantial electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 41 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…Similarly for PA, the linear regression equation for oxidation peak currents and reduction peak currents were I pa (μA) = 0.0755υ + 14.153 with correlation coefficient of 0.982 and I pc (μA) = À 0.034υ-8.64 with correlation coefficient of 0.980, respectively. These studies confirmed that the current produced by the electro-chemical redox processes of DA and PA at Poly-ET/GCE was surface controlled one [33,34].…”
Section: Effect Of Scan Ratesupporting
confidence: 69%
“…Similarly for PA, the linear regression equation for oxidation peak currents and reduction peak currents were I pa (μA) = 0.0755υ + 14.153 with correlation coefficient of 0.982 and I pc (μA) = À 0.034υ-8.64 with correlation coefficient of 0.980, respectively. These studies confirmed that the current produced by the electro-chemical redox processes of DA and PA at Poly-ET/GCE was surface controlled one [33,34].…”
Section: Effect Of Scan Ratesupporting
confidence: 69%
“…For these reasons, the identification of MTZ in water and soil environments is of importance to researchers. Until now, many approaches have been reported for analysis of MTZ, such as fluorescence techniques, gas chromatography, ion mobility spectrometry, polarography detection, high-performance liquid chromatography, flame ionization detection, mass spectrometry, and UV spectrophotometry. However, the aforementioned methods are restrictive in being time-consuming, costly, limited in selectivity, and complex. Conversely, electrochemical techniques are a superior choice because of the ease of onsite methodologies, the possibility of miniaturization, low expense, amenable monitoring, sensitivity, portability, and speed which have attracted considerable attention. …”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) graphene materials which can be assembled by graphene nanosheets, have improved physical and electrochemical properties when compared to graphene nanosheets [24][25][26]. In recent years, they have gained great attention because of their high specific surface area, good electron mobility, porous, and 3D-networked structure [27][28][29]. Graphene hydrogel (GH) is a 3D graphene material that can be prepared easily by hydrothermal reduction [30][31][32] and chemical reduction [33,34].…”
Section: Introductionmentioning
confidence: 99%